Report of a Working Group on Forages (Second Meeting): Held in Carlow, Ireland 7-11 Oct. 1985 - International Board for Plant Genetic Resources; United Nations Development Programme (1985)
Report of the ECPGR Forages Working Group meeting, second meeting, 7-11 October 1985, Carlow, Ireland